2016
DOI: 10.1038/srep19224
|View full text |Cite
|
Sign up to set email alerts
|

The parasitic worm-derived immunomodulator, ES-62 and its drug-like small molecule analogues exhibit therapeutic potential in a model of chronic asthma

Abstract: Chronic asthma is associated with persistent lung inflammation and long-term remodelling of the airways that have proved refractory to conventional treatments such as steroids, despite their efficacy in controlling acute airway contraction and bronchial inflammation. As its recent dramatic increase in industrialised countries has not been mirrored in developing regions, it has been suggested that helminth infection may protect humans against developing asthma. Consistent with this, ES-62, an immunomodulator se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 56 publications
(113 reference statements)
2
52
0
Order By: Relevance
“…ES-62 is a PC-containing immunomodulatory glycoprotein that exhibits protective effects in models of allergic and autoimmune disease911 by homeostatically resetting the effector: regulatory B cell balance and consequently modulating the IL-23/IL-17/IL-22 inflammatory axis2345630, dysregulation of which has been implicated in the pathogenesis of chronic inflammatory disorders31. Although the precise cellular networks modulated by the worm product appear to differ depending on the inflammatory context, ES-62 likely affords protection by acting to subvert TLR signalling via partial downregulation of MyD88 expression in effector cells of both innate and adaptive immunity346917.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ES-62 is a PC-containing immunomodulatory glycoprotein that exhibits protective effects in models of allergic and autoimmune disease911 by homeostatically resetting the effector: regulatory B cell balance and consequently modulating the IL-23/IL-17/IL-22 inflammatory axis2345630, dysregulation of which has been implicated in the pathogenesis of chronic inflammatory disorders31. Although the precise cellular networks modulated by the worm product appear to differ depending on the inflammatory context, ES-62 likely affords protection by acting to subvert TLR signalling via partial downregulation of MyD88 expression in effector cells of both innate and adaptive immunity346917.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise cellular networks modulated by the worm product appear to differ depending on the inflammatory context, ES-62 likely affords protection by acting to subvert TLR signalling via partial downregulation of MyD88 expression in effector cells of both innate and adaptive immunity346917. The effect of targeting this key integrator of inflammatory signalling is exemplified by the ability of ES-62 to suppress both the priming and maintenance of pathogenic Th17 and IL-17-producing γδ T cells in CIA by targeting MyD88 in both DCs and Th17 cells49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that a single, defined ES protein, ES-62, can resolve chronic inflammation by normalising aberrant MyD88 signalling to homeostatically restore immunoregulation, irrespective of the inflammatory phenotype [4,5,[10][11][12]. MyD88 is increasingly recognized not only as a key innate immune system receptor transducer but also as an integrator of dysregulated inflammatory and metabolic pathways [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the best characterised ES products is ES-62, a phosphorylcholine (PC)-containing glycoprotein secreted by the rodent filarial nematode Acanthocheilonema viteae that we have shown to prevent initiation and progression of pathology in mouse models of certain allergic (asthma, contact dermatitis) and autoimmune (RA, SLE) inflammatory diseases 1,2,[38][39][40][41][42][43] . Collectively, our studies have identified a unifying mechanism of action that allows effective protection irrespective of the inflammatory phenotype: thus, by subverting TLR4 signalling to downregulate aberrant MyD88-responses, ES-62 acts to homeostatically reset the regulatory:effector immune cell balance, primarily to restore levels of IL-10 + regulatory B cells (Bregs) and suppress pathological IL-17-driven inflammation 1,2,[38][39][40][41][42][43][44] . In experimental models of RA and human disease, perturbation of the microbiota has been shown to disrupt the balance of pathogenic Th17 cells and the counter-regulatory Bregs and Tregs that act to homeostatically resolve inflammation 20,[24][25][26] .…”
Section: Introductionmentioning
confidence: 99%